Risk factors for sudden cardiac death in childhood hypertrophic cardiomyopathy: A systematic review and meta-analysis. (29th August 2020) - Norrish, Gabrielle; Cantarutti, Nicoletta; Pissaridou, Eleni; Ridout, Deborah A; Limongelli, Giuseppe; Elliott, Perry M; Kaski, Juan Pablo
Abstract: Aims: To perform a systematic literature review and meta-analysis of clinical risk factors for sudden cardiac death (SCD) in childhood hypertrophic cardiomyopathy. Methods: Medline and PubMed databases were searched for original articles published in English from 1963 through to December 2015 that included patients under 18 years of age with a primary or secondary end-point of either SCD or SCD-equivalent events (aborted cardiac arrest or appropriate implantable cardioverter–defibrillator discharge) or cardiovascular death (CVD). Results: Twenty-five studies (3394 patients) met the inclusion criteria. We identified four conventional major risk factors that were evaluated in at least four studies and that we found to be statistically associated with an increased risk of death in at least two studies: previous adverse cardiac event (pooled hazard ratio [HR] 5.4, 95% confidence interval [CI] 3.67–7.95, p  < 0.001); non-sustained ventricular tachycardia (pooled HR 2.13, 95% CI 1.21–3.74, p  = 0.009); unexplained syncope (pooled HR 1.89, 95% CI 0.69–5.16, p  = 0.22); and extreme left ventricular hypertrophy (pooled HR 1.80, 95% CI 0.75–4.32, p  = 0.19). Left atrial diameter did not meet the major risk factor criteria; however, this is likely to be an additional significant risk factor. 'Minor' risk factors included a family history of SCD, gender, age, symptoms, electrocardiogram changes, abnormal blood pressure response to exercise and left ventricular outflow tract obstruction. Conclusions: A lack of well-designed, large, population-based studies in childhood hypertrophic cardiomyopathy means that the evidence base for individual risk factors is not robust. We have identified four clinical parameters that are likely to be associated with increased risk of SCD, SCD-equivalent events or CVD. Multi-centre prospective studies are needed in order to further determine the relevance of these factors in predicting SCD in childhood hypertrophic cardiomyopathy and to identify novel risk markers. Condensed abstract: A systematic review and meta-analysis of clinical risk factors predicting sudden cardiac death in childhood hypertrophic cardiomyopathy was performed, identifying four 'major' factors: previous adverse cardiac event; non-sustained ventricular tachycardia; syncope; and extreme left ventricular hypertrophy. Well-designed multi-centre studies are required in the future in order to confirm these findings.